SINTESIS PUPUK LEPAS LAMBAT BERBASIS KITOSAN-BIOCHAR-UREA SEBAGAI MATERIAL POTENSIAL PELEPASAN NITROGEN - Karbeka, Martasiana; Mautuka, Zakarias Adrianto; Lily, Diana Oktovina Tung (Lantanida Journal, 2024)
The fabrication of slow-release urea fertilizer beads using chitosan and chitosan-biochar as coating materials has been accomplished. The beads were synthesized by solidifying chitosan-urea and chitosan-biochar-urea hydrogels in a NaOH solution. Characterization of the chitosan-urea composite beads (BKU) and chitosan-biochar-urea beads (BKBU) was conducted through Fourier-transform infrared (FTIR) spectroscopy, along with water intake (swelling) and nitrogen release tests in aqueous media at time intervals of 24, 72, 120, and 168 hours. The FTIR spectra of BKU and BKBU beads displayed functional group peaks associated with biochar (hydroxyl and carboxylate), chitosan (amine and hydroxyl), and urea (amine and carbonyl), along with others supporting group. Water intake rates were 72% for BKU and 81% for BKBU, which impacted nitrogen release patterns. BKU exhibited a faster nitrogen release compared to BKBU, indicating that BKBU is more suitable for use as a slow-release fertilizer due to its more gradual nitrogen release mechanism